CENGO: A Web-Based Serious Game to Increase the Programming Knowledge Levels of Computer Engineering Students - Güleç, Ulaş; Yilmaz, Murat; Yalcin, Alihan Dogus; O’Connor, Rory V.; Clarke, Paul M. (Springer Verlag, 2019)
In recent years there has been an increased use of serious games to help increase the level of knowledge and experience of individuals working in different domains. In particular serious games for educational purposes have been used in many domains including software engineering and computer science [1]. Hence, this study proposes a quantitative research approach to increase the programming knowledge levels of the first-year undergraduate students at computer engineering departments. For this aim, a responsive web platform was developed to teach the syntax and logic of the C programming language by using game elements. This environment provided students with an ability to independently investigate the C programming language continuously since the platform is always accessible. To better understand the effectiveness of the designed environment, 10 first-year computer engineering students were selected as a pilot experimental group. According to the results obtained from the user tests, this game can be used as an educational tool, which supports the traditional training methods, to increase the knowledge levels of students about the syntax and logic of the C programming language.
Keywords: Continuous education; Personal improvement; Serious games